Perception towards Digital Mode of Teaching at Higher Education: A Qualitative Research - Poudel, K. (Pragya Darshan प्रज्ञा दर्शन, 2024)
This article aims to explore the perception towards the digital mode of teaching at higher education for enhancing the quality education needed for 21st century. To achieve this objective, the researcher followed the qualitative research design. Altogether 10 teachers, 5 students and 2 IT experts were chosen as a sample population following the purposive sampling technique. Similarly, FGD, in depth interview and document analysis were main tools for collecting authentic data in the concerned area. Additionally, collected data were edited, transcribed, coded and thematized in a systematic way. Furthermore, the researcher triangulated the date to get meaningful results and conclusions. Finally, this study identified that the digital pedagogy have been creating new opportunities to seek and share information more easily. In the same vein, the government should focus on strengthening the digital pedagogy in all educational institutions. As a result, Digital technologies can support learning by providing necessary information at a convenient place and suitable time. The universal crisis demands the change in education sectors all over the world due to facing the bad situation of Covid pandemic. It caused a rising interest in the use of digital mode of teaching those who are staying in remote area.